Modeling habitat use of the threatened and endemic mara (Dolichotis patagonum, Rodentia, Caviidae) in agricultural landscapes of Monte Desert - Rodriguez, Maria Daniela (2009)
Effective management of natural populations depends heavily on the capacity for understanding and predicting their habitat requirements. For endemic and threatened species like the mara (Dolichotis patagonum), this information is extremely necessary for populations survival. I investigated and constructed a mathematical habitat model for the mara, with the capacity to predict the probability of finding animals in a particular environment. In the Monte Desert, maras prefer habitats with low shrub density and high percentage of bare soil. The area used by each couple of maras was 7.73 ha and shows an aggregation pattern. Contrary to expectation, about 94% of these areas were in habitats created by human activities. Grazed, burned and crop areas seem to be prefered by maras when natural open habitat disappear. This information and the results of habitat requirements can be used to monitor the status of mara populations and predict potential population extinctions according to habitat variables.